Natural resource management and institutional change - Carney, Diana (Routledge Research/ODI development policy studies., 1998)
Using new evidence from a three year programme of research in developing countries in Asia, Latin America and Africa, the authors describe how government organizations have been privatised, decentralised or restructured while private sector organizations - both non-profit and commercial - have taken on increasingly important roles in resource management and service supply. This book provides an important and easily accessible point of reference for decision-makers and students alike, offering unique view in its breadth of coverage across the natural resources sector and a range of differe.